Pengaruh Kitosan Iradiasi dalam Menurunkan Kadar Gula Darah Mencit Jantan Swiss Webster dengan Metode Tes Toleransi Glukosa Oral - SESILIA ANDRIANI KEBAN; SWASONO R. TAMAT R. TAMAT (Fakultas Farmasi Universitas Pancasila, 2014)
Chitosan is a dietary iber that has been used as an antihyperglycemia agent. Irradiation of chitosan resulted in 1,4-β glycosidic chain termination which shortened the chitosan chains, lower its molecular weight, and minimize steric effects. This is a preliminary experimental study to ind the effective irradiation dose and chitosan type in lowering blood sugar levels. Fifty two mice were used in this research and divided into various treatment groups which included: normal control, negative control, positive control (Acarbose), non-irradiated chitosan and irradiated chitosan. Chitosan solution were given for 15 days and then oral glucose tolerance test were conducted using 1.5 g/kg bw of glucose. Blood sugar levels were monitored at minute 0, 30, 90, 120, and 150; and Area Under the Curves (AUC) were calculated. The results showed that the irradiation of chitosan can lower blood sugar levels greater than the non-irradiated chitosan; and chitosan irradiation of 100 kGy dose I and II can lower blood sugar levels better than irradiated chitosan and positive control. It was concluded that although the 100 kGy irradiated chitosan appears to have greater ability than the positive control group in lowering blood sugar levels. But after LSD test towards the AUC value, it appears that both groups have the same effectivity.